Surgical Effectiveness of Uniportal-VATS Lobectomy Compared to Open Surgery in Early-Stage Lung Cancer - Nachira, Dania; Congedo, Maria Teresa; Tabacco, Diomira; Sassorossi, Carolina; Calabrese, Giuseppe; Ismail, Mahmoud; Vita, Maria Letizia; Petracca-Ciavarella, Leonardo; Margaritora, Stefano; Meacci, Elisa (Frontiers in Surgery, 2022)
Background Although the feasibility and safety of Uniportal-Video-Assisted thoracic surgery (U-VATS) has been proven, its surgical effectiveness is still debated. The aim of this study is to assess the equivalence of the U-VATS approach compared with an open technique in terms of surgical (nodal-upstaging, complications, and post-operative results) and short-term survival outcomes. Methods The clinical data of patients undergoing lobectomy for NSCLC at our center, from January 2014 to December 2019, were analyzed retrospectively. All patients undergoing open or U-VATS lobectomy with lymphadenectomy for early-stage lung cancer (cT1-T3N0, stages IA-IIB) were included in the study. Only 230 patients satisfied the inclusion criteria. Group bias was reduced through 1:1 propensity score matching, which resulted in 46 patients in each group (open surgery and U-VATS). Results The intra- and post-operative mortality were null in both groups. There was no difference in the post-operative complications (p: 1.00) between U-VATS and open lobectomy. There was also no recorded difference in the pathological nodal up-staging [11 (23.9%) after thoracotomy vs. 8 (17.4%) after U-VATS, p: 0.440). The chest tube duration was longer in the open group (p: 0.025), with a higher post-operative pain (p: 0.001). Additionally, the 3-year overall survival (OS) was 78% after U-VATS lobectomy vs. 74% after open lobectomy (p: 0.204), while 3-year disease-specific survival (DSS) was 97 vs. 89% (p: 0.371), respectively. The 3-year disease-free survival (DFS) was 62% in the U-VATS group and 66% in the thoracotomy group, respectively (p: 0.917). Conclusions Uniportal-VATS lobectomy for the treatment of early-stage lung cancer seems to be a safe and effective technique with similar surgical and short-term survival outcomes as open surgery, but with lower post-operative pain and shorter in-hospital stay.